2023
DOI: 10.3171/2023.3.focus2380
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of motion during microvascular anastomosis simulation using machine learning hand detection

Abstract: OBJECTIVE Microanastomosis is one of the most technically demanding and important microsurgical skills for a neurosurgeon. A hand motion detector based on machine learning tracking technology was developed and implemented for performance assessment during microvascular anastomosis simulation. METHODS A microanastomosis motion detector was developed using a machine learning model capable of tracking 21 hand landmarks without physical sensors attached to a surgeon’s hands. Anastomosis procedures were simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Mastery of this technique requires extensive training, dedication, and persistence. In light of this, Gonzalez-Romo et al conducted a comprehensive investigation into hand motion during microvascular anastomosis, utilizing a CNN to track 21 hand positions [112]. The study involved six participants, including two experts, two intermediates, and two novices, with no physical constraints imposed on their hand movements.…”
Section: Vascularmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastery of this technique requires extensive training, dedication, and persistence. In light of this, Gonzalez-Romo et al conducted a comprehensive investigation into hand motion during microvascular anastomosis, utilizing a CNN to track 21 hand positions [112]. The study involved six participants, including two experts, two intermediates, and two novices, with no physical constraints imposed on their hand movements.…”
Section: Vascularmentioning
confidence: 99%
“…Asadi et al demonstrated the superiority of machine learning in predicting outcomes for brain arteriovenous malformations, but limitations include the dependency on large training datasets and the risk of overfitting [111]. Gonzalez-Romo et al developed a machine learning-based hand motion detector for microvascular anastomosis simulation, but limitations include the small sample size and the need for further validation and clinical application [112].…”
Section: Current Challengesmentioning
confidence: 99%